TINJAUAN HUKUM KEDUDUKAN AKTA HIBAH WASIAT YANG MELAMPAUI BAGIAN MUTLAK AHLI WARIS LEGITIMARIS: LEGAL REVIEW OF THE POSITION OF THE WISDOM OF WISDOM THAT EXCEEDS THE ABSOLUTE SECTION OF LEGITIMARY HERITAGES - Imam, Imam; Kamsilaniah; Tira, Andi (Faculty Of Law Bosowa University, 2022)
This study aims to determine and analyze the position of the will of the heirs to the absolute part of the heirs. The research method used is qualitative legal research. The types and sources of data consist of primary data in the form of laws and regulations, and Court Decisions as well as secondary legal materials consisting of books, articles and journals related to this research. The entire legal material is collected in a structured systematic manner using qualitative measures and presented in a descriptive analysis. The results of the study indicate that a will or testamental grant that violates the